Pengelolaan Limbah Organik Home Industry Ditinjau Dari Perspektif Hukum Lingkungan - Firnanda Agmilya Mukhibudin; Nur Qoilun (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The issue of organic waste management in the home industry sector is a critical concern in environmental law due to the high potential for pollution resulting from small-scale production activities that are not yet fully managed in a systematic manner. This study aims to analyze the implementation of environmental law in organic waste management and to develop policies that are more adaptable to the characteristics of microenterprises. The research method employed is a legal-empirical approach, examining applicable legal norms such as Law No. 18 of 2008 on Waste Management and Government Regulation No. 22 of 2021, supplemented by field data collected through interviews with business operators at Agmilya Tea in Gresik Regency. The research results indicate that organic waste management practices have been carried out independently through a circular economy approach, such as the utilization of waste into natural fertilizers and pesticides; however, these practices have not yet been formally integrated into the regulatory system. The discussion highlights a gap between legal norms and implementation caused by technical and economic constraints, as well as bureaucratic complexity. Therefore, a reconstruction of environmental legal policies is needed one that is simpler, more practical, and grounded in empirical reality to enhance legal effectiveness and promote environmental sustainability in the home industry sector.